KONSEPTUALISASI VALUE CO-CREATION DALAM KONTEKS CUSTOMER TO CUSTOMER - Buana, Yud; Isanawikrama, Isanawikrama; Hutomo, Edwin Joyo; Kurniawan, Yohanes Jhony (Universitas Bunda Mulia, 2019)
This research is conceptual thinking according to the approach from a customer-dominant logic (C-D) perspective, this study aims to expand the discussion of value co-creation by providing conceptual insights into value co-creation within the customer's social environment. In the social context in which customers consume together or collectively, research will raise the concept of how to provide recommendations on how services can facilitate value co-creation in a customer-to-customer (C2C) context. Current thinking about value in C-D according to the service management perspective on C2C interactions and social science concepts in consumers, requires a framework that can be proposed for C2C value co-creation as a dynamic, gradual process. Values appear in four different social layers: